Klausul Bahasa dalam Kontrak: Analisis Surat Edaran Mahkamah Agung Nomor 3 Tahun 2023 - Ilhamsyah; Sudirman; Wahyudi Umar (CV Rewang Rencang, 2024)
Language clauses in contracts are a crucial element that is often overlooked in Indonesian legal practice. With a statute and conceptual approach, this study analyzes the Supreme Court Circular Letter Number 3 of 2023, which provides guidelines regarding the use of language in contracts. The study results show that using clear and simple language in contracts can reduce the risk of disputes and increase trust between the parties involved. In addition, this study recommends the need for the consistent implementation of language standards to support legal integration and create a more stable business environment. Thus, this research contributes to developing contract law in Indonesia and provides insights for academics and legal practitioners.